PENGARUH KONTEN YOUTUBE AGRIBISNIS TERHADAP MOTIVASI BERWIRAUSAHA MAHASISWA FAKULTAS PERTANIAN UNIVERSITAS UDAYANA - Muhammad Rafi Alhabib; Gede Mekse Korri Arisena (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
This study aims to investigate the effect of agribusiness YouTube content on the entrepreneurial motivation of students in the Faculty of Agriculture, Udayana University. The sample consisted of 94 students selected through the Proportional Stratified Random Sampling method. Data was collected using a questionnaire and analyzed using quantitative descriptive analysis and Structural Equation Model-Partial Least Squares (SEM-PLS). The results showed that the level of interest, response, and purpose of watching agribusiness content on YouTube and the entrepreneurial motivation of agriculture faculty students were categorized as good. One variable (purpose of watching agribusiness content on YouTube) showed that agribusiness content on YouTube had a significant effect on the entrepreneurial motivation of agriculture faculty students, 2 variables (interest and response to watching agribusiness content on YouTube) showed that agribusiness content on YouTube had a not significant effect on the entrepreneurial motivation of agriculture faculty students.